Analytical Hierarchy Process: a method for Determining the Assessment of Soft Skill Competence - Rizwan Sai; William Ramdhan; Masitah Handayani (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Analytical Hierarchy Process (AHP) is a method that is often used to determine decisions in system making. To determine the soft-skill competence possessed by a person, a more in-depth analysis needs to be carried out based upon the criteria used. The purpose of this study is to produce a decision support system to assess the soft-skill competence of employees using the AHP method. This system is made based on the stages of the waterfall model which consists of analysis, design, implementation and testing. The collection technique used observation and interviews, and the amount of data was 18 people who were analyzed using the AHP method. System testing is done with a black box which aims to see the functionality to the system. Our findings are in the form of a web-based decision support system. In addition, this system managed to show the best employee with a score of 0.622, and all components run as expected, without any errors. So that this system can be used as a reference to determine the soft skill competencies of employees in this place.